The impacts of technological innovation on regulatory structure: Fintech in post-crisis Europe (2020)
pecific forms of digitised financial innovation have been the subject of several chapters in this volume: Chapter 2 studied the regulation of high-frequency trading and Chapter 3 the role of clearing houses and central depositories in derivatives trading. In this chapter, we examine technological innovation more broadly and in its own right, considering its impact on European regulatory structures in recent years. How does technological innovation, or ‘Fintech’,1 in major financial markets – currencies, payment systems, capital markets, alternative intermediaries and insurance – impact upon regulation?